ASSOCIATION BETWEEN SALT INTAKE AND URIC ACID, AND ITS INTERACTION ON THE INCIDENCE OF PREHYPERTENSION AMONG CHINESE YOUNG ADULTS. (June 2018) - Wang, Y.; Hu, J.W.; P.F.Qu,; Wang, K.K.; Yan, Y.; Chu, C.; Zheng, W.L.; Xu, X.J.; Lv, Y.B.; Ma, Q.; Gao, K.; Yuan, Y.; et al.
Abstract : Objective: High uric acid (UA) level and high salt intake are reportedly associated with cardiovascular disease. This study investigated the association between UA and daily salt intake, as well as its interaction on the risk of prehypertension. Design and method: A total of 1869 participants without hypertension were recruited from a previously established cohort in Shaanxi Province, China. The participants were classified as normotensive or prehypertensive on the basis of their blood pressure. Salt intake was estimated from early-morning urine specimens using an equation validated for this study population. Results: Increasing quartiles of salt intake were associated with high urinary UA/creatinine levels in prehypertensive participants (from quartile 1 to quartile 4: 0.12, 0.17, 0.24, and 0.33, P for trend < 0.001)). Estimated salt intake positively correlated with urinary UA/creatinine excretions in the prehypertensive group (r = 0.496; P < 0.001). In addition, the prehypertensive group had higher levels of salt intake and serum UA than the normotensive group [salt intake: 13.22 ± 3.52 vs. 12.35 ± 3.42 g/day, P < 0.001; serum UA: 290.0 (233.6–340.6) vs. 255.6 (211.6–305.0) μmol/L, P < 0.001]. The multivariate-adjusted odds ratios (95% confidence interval) for prehypertension compared with normotension were 1.68 (1.27–2.22) for salt intake and 1.71 (1.21–2.42) for serum UA. Increasing salt intake and serum UA were associated with higher risk of prehypertension. Compared with the lowest quartiles, the highest salt intake and serum UA quartiles entailed 3.48 times greater risk of prehypertension. Figure. No caption available. Conclusions: Salt intake is associated with urinary UA excretion in prehypertensive participants. High levels of salt intake and serum UA simultaneously are associated with a higher risk of prehypertension.